Pelestarian Budaya Melalui Keterampilan Anyaman Katidiang Sebagai Upaya Pemberdayaan Masyarakat - Khairunnisa, Gisandha (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 22 No 2 (2022)DO - 10.24843/PJIIB.2022.v22.i02.p06, 2022)
Katidiang is a basket that is usually made of blades or bamboo that is split open so that it becomes a strand which is then woven into a basket shape and so on. Katidiang in other areas is usually also made of pandan leaves, but in Jorong Tabek Panjang Katidiang is made using blades. Katidiang webbing is usually used by the community for various things, ranging from a place to be brought to the market such as a place for vegetables, fruits, tubers. In addition, Katidiang is also used by the community as a place for rice when people harvest rice in the fields. The purpose of writing this article is to provide ideas about community empowerment through training to make katidiang so that it can become a livelihood for the community and to be able to preserve the habit or culture of making katidiang people in Jorong Tabek Panjang.